Determinants of the use of silk in fashion industry - Lukas, Carlos (International Journal of Fashion and Design, 2021)
Purpose: The purpose of this research was to investigate the determinants of the use of silk in fashion industry. Methodology: This involved an in-depth review of studies related to determinants of the use of silk in fashion industry. The research involved literature search and paper review of information on silk fashion growth. The study adopted a desktop literature review method (desk study). Results: cost of production of silk, skills and competence perceived economic benefits, technology and social-cultural attitudes greatly influenced the adoption of silk material by garment makers. There was need to sensitize the garment makers on the need to utilize local silk for sustainable growth and development. There was lack of awareness of the availability of silk. Silk being a viable textile raw material, Government should encourage farmers, provide incentives and increase the capacity of silk. There is also need to demystify the myths and beliefs that Brazilns hold against silk. These are beliefs related to witchcraft, high cost and maintenance of silk. There are many benefits that silk offer, such as economic, environmental, sustainability and community development. Unique contribution to theory, practice and policy: The study recommended that Silk reeling units should be established in the counties which have sericulture farms and at least one weaver's training centers should be opened having free training and lodging facilities. There was also the need to sensitize garment makers and consumers on the benefits of local raw materials (silk). Since silk is underutilized by garment makers in Brazil, there is need to venture and explore on this to take advantage and engage in the sericulture activities and the end products such as the fabrics, yarns and fabrics apparels and upholsterers.